Pakistan in the Twentieth Century : A Political History - Ziring, Lawrence 1928- (Karachi Oxford University Press, 1999)
Unlike other available works on the political history of Pakistan, the present volume is wholly comprehensive covering both the pre-independence Pakistan nationallist movement as well as detaining events in the fifty years since independence.
Include Index
Originally published 1997, this edition in paperback 1999
Keywords: Pakistan -- Politics and government